EXPLORING THE USE OF CHATGPT AND ITS IMPACT ON STUDENTS’ ENGLISH WRITING - Hafsa, Hafsa; Noni, Nurdin; Samtidar, Samtidar (Universitas Negeri Makassar, 2026)
This study investigates the use of ChatGPT to assist students in English writing classes, specifically in the Paragraph Writing course at UNM Parangtambung. The objectives of the research are to explore: (1) how ChatGPT supports students in English writing classes, and (2) the impact of using ChatGPT on students’ writing. A descriptive qualitative method was employed, with data collected through classroom observations and semi-structured interviews involving one English lecturer and students from class E24 at UNM Parangtambung. The findings reveal that: (1) students use ChatGPT to help generate ideas, construct sentences, and improve efficiency in completing writing tasks; (2) most students acknowledged that ChatGPT facilitates the writing process by providing quick references, enriching vocabulary, and offering feedback; (3) however, students were also aware of ChatGPT’s limitations, such as the use of complex language, occasional inaccuracies, the need for lecturer validation, and ethical concerns regarding student dependence on ChatGPT, which may reduce critical thinking skills and interest in reading. The study concludes that while ChatGPT is considered helpful in addressing writing challenges and enhancing learning motivation, it cannot replace the essential role of lecturers in the teaching and learning process.